3D ear alignment based on geometry invariant - Taertulakarn, S.; Tosranon, P.; Pintavirooj, C. (My University, 2016)
Nowadays, ear shape study is one of the most significant trends in the biometric research. In this study, we present a novel surface fiducial point's detection that is computed from the differential surface geometry. The fiducial points are intrinsic, local, and relative invariants, i.e., they are preserved under similarity, affine, and nonlinear transformations that are piecewise affine. In our experiment, the fiducial points are used in a non-iterative geometric-based method for 3D ear alignment. The matching is achieved by establishing correspondences between fiducial points after a sorting based on a set of absolute local affine invariants derived from them. Experimental results showed that our purposed surface feature is suitable for further application to 3D ear identification.
Keywords: 3D ear alignment; Surface geometric invariant; Zero torsion